A construção da empregabilidade para uma mulher transexual - Bonotto, Natália Rissinger (2020)
This research aims to study the process of employability for a transsexual woman. A discussion was set about transsexualization in the context of family and formal learning. An interview with a trans woman was undertaken for analysis. Two dialogic maps were made to organize the visibility of the dialogue. Thereafter two narrative lines were created for time passing and transformation processes of the interviewee. The theoretical-methodological approach of discursive psychology - developed in the Nucleus of Studies on Discursive Practices in Daily Life: rights, risks and health (NUPRAD/PUC-SP) - was used to reach the objective, as part of a constructionist approach. In general, the results indicate that there are difficulties in the formal employability for trans people and the main problem is the institutionalized transphobia. Nevertheless, there are many trans people working in formal jobs although the literature about this population seems to prefer to disclose the difficulties and problems that affect them to create an unique discourse of suffering and failure